Diagnosis Kesulitan Belajar Bahasa Indonesia Dalam Menulis Karangan Siswa Kelas X SMAN 1 Keruak Tahun Pelajaran 2018/2019 - Murbaya, Muh. Progo (FAKULTAS TARBIYAH, 2020)
This study aims to find out what aspects of students' learning difficulties in writing essays and to find out the efforts made by teachers to find out students' learning difficulties in writing essays. The type of this research is experimental, namely research conducted by carrying out certain treatments (treatments) on the subject followed by measurements of the effects of the treatment to determine the causal relationship (cause and effect) between two or more phenomena. The analytical method used in this research is the descriptive quantitative method. Quantitative descriptive methods are used to process data in order to: (1) obtain statistical measures such as the mean, median, mode, and standard deviation, (2) compile score classifications or compile frequency distributions, (3 ) calculate the percentage. The results of the study found that some students had difficulty in each sub-topic, especially in the word/diction sub-subject. The percentage of students' difficulties in learning Indonesian in writing essays is in the sub-topic of word/diction choice, there are 67.78% and in the paragraph sub-subject 65.56% which in general students have difficulty. Efforts have been made by the teacher, namely by dividing students into groups according to sub-subjects that have not been understood and giving assignments to each group. Then additional lessons are also given in the afternoon on a scheduled basis